Issues and challenges face by Majlis Agama Islam Perak (MAIPK) in managing and developing waqf lands / Nurul Asma Husna Ramlan and Nur Baizura Mohd Shukor - Ramlan, Nurul Asma Husna; Mohd Shukor, Nur Baizura (2019)
Waqf is one of the sources that able to generate economic in term of revenues and incomes for ummah. Unfortunately, waqf today perceived and understood to be very narrow, unmodern, non-economic, antisocial and resolves only around religious issues. Thus, it is a great challenge for Waqf institution in this country to participate a role in uplifting the pride, dignity and supremacy of Islam in Malaysia. As well as MAIPk who is also having problems in managing and developing its waqf lands. Therefore, this paper aim to focus on identifying the issues and challenges face by MAIPk in managing and developing waqf lands in Perak. To come out with a proper finding, a qualitative method has been applied by carried out interview with few expert panels. Finding showed, the issues and challenges identified from this study are; legal constraints, financial, unsuitability of land & no commercial value and oral waqf. The significant impact from this study is able to improve the management and development of waqf lands and generate economic growth to the state of Perak.